2000
DOI: 10.1074/jbc.m909099199
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Focal Adhesion Kinase in Phenylephrine-induced Hypertrophy of Rat Ventricular Cardiomyocytes

Abstract: A variety of agonists including phenylephrine (PE) induce hypertrophy in neonatal ventricular cardiomyocytes. Here we report that signals provided by extracellular matrix proteins (ECM) augment the PE-induced hypertrophic response of cardiomyocytes and provide evidence that ECM-dependent signaling is mediated in part by the protein tyrosine kinase, focal adhesion kinase (FAK). Addition of PE to cultured neonatal cardiomyocytes stimulated sarcomeric organization, increased cell size, and induced atrial natriure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
3
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 42 publications
6
105
3
7
Order By: Relevance
“…5,28 This effect is partially explained by PE-induced rapid tyrosine phosphorylation of costamere complex proteins, including focal adhesion kinase (FAK), paxillin and p130 Crk-associated substrate, 28 an effect dependent on intact integrin and FAK functions. Our data demonstrate that PE also synergizes with FN in inducing increased costamere localization of ILK and PIPcomplex proteins, suggesting that these proteins play a role in hypertrophic signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,28 This effect is partially explained by PE-induced rapid tyrosine phosphorylation of costamere complex proteins, including focal adhesion kinase (FAK), paxillin and p130 Crk-associated substrate, 28 an effect dependent on intact integrin and FAK functions. Our data demonstrate that PE also synergizes with FN in inducing increased costamere localization of ILK and PIPcomplex proteins, suggesting that these proteins play a role in hypertrophic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…24 Interestingly, ILK and IPAP1 complex assembly are required for cytoskeletal association of paxillin in epithelial cells 14 and a significant increase in ILK mRNA has been observed in a pressure-overload mouse model of cardiac hypertrophy. 25 Studies from our laboratory 26 and others 27,28 have demonstrated that FN induces cardiac myocyte hypertrophy in neonatal rat ventricular myocytes (NRVM). Moreover, FN-induced hypertrophy depended on intact integrin signaling, as evidenced by inhibition with anti-b1-integrin antibody, [26][27][28] and potentiated hypertrophy induced by the alphaadrenergic agonist PE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adenovirus-green fluorescent protein (Ad-GFP) and Adenovirus Green fluorescent protein-FRNK fusion protein (Ad-GFP-FRNK), which were produced as previously described (Taylor et al 2000), were a gift from Joan Taylor (University of North Carolina-Chapel Hill). A control adenovirus lacking an insert (Ad-Empty) was generated by us as previously described (Kornberg, 2005).…”
Section: Adenovirusmentioning
confidence: 99%
“…In the integrin initiating signaling pathway, clustering of integrins leads to the recruitment of FAK to the newly formed focal adhesion which results in auto‐phosphorylation and concomitant activation of FAK 30, 32. A recent study supported a role for integrin‐mediated signaling through FAK in the development of cardiac hypertrophy 33. Furthermore, Aikawa and his colleagues demonstrated that the activation of integrin‐FAK might be necessary for stretch‐induced hypertrophic responses 34.…”
Section: Discussionmentioning
confidence: 99%